2020
DOI: 10.21203/rs.3.rs-98575/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Curcumin Suppresses Tumorigenesis via Promoting SLC1A5-mediated Ferroptosis in Breast Cancer

Abstract: Background: Breast cancer is one of the most malignant tumors in the female. Previous studies confirmed that Curcumin, a kind of polyphenol compound extract from the Curcuma longa underground rhizome, inhibits the survival of cancer cells. However, the functional role and mechanism of curcumin in breast cancer remain unclear.Methods: The cell counting kit-8 (CCK-8) assay was performed to examine the effect of curcumin on cell viability in both MDA-MB-453 and MCF-7 cells. Determination of lipid reactive oxygen … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 45 publications
(52 reference statements)
0
1
0
Order By: Relevance
“…93 A similar study showed that upregulation of solute carrier family 1 member 5 (SLC1A5) in breast cancer cells has a role in the induction of ferroptosis and suppression of tumourigenesis. 94 In addition to breast cancer cells, the anticancer effect of curcumin through induction of ferroptosis has been observed in lung cancer cells. Treatment of two different lung cancer cell lines including A549 and H1299 cells confirmed the tumoursuppressive effect of curcumin through induction of ferroptosis.…”
Section: Ferroptosismentioning
confidence: 99%
“…93 A similar study showed that upregulation of solute carrier family 1 member 5 (SLC1A5) in breast cancer cells has a role in the induction of ferroptosis and suppression of tumourigenesis. 94 In addition to breast cancer cells, the anticancer effect of curcumin through induction of ferroptosis has been observed in lung cancer cells. Treatment of two different lung cancer cell lines including A549 and H1299 cells confirmed the tumoursuppressive effect of curcumin through induction of ferroptosis.…”
Section: Ferroptosismentioning
confidence: 99%